Construction of novel pJRD215-derived plasmids using chloramphenicol acetyltransferase (cat) gene as a selection marker for Acidithiobacillus caldus. - Rui Wang; Chunmao Lin; Jianqiang Lin; Xin Pang; Xiangmei Liu; Chengjia Zhang; Jianqun Lin; Linxu Chen (PLoS ONE)
Background Acidithiobacillus caldus, a Gram-negative, chemolithotrophic sulfur-oxidizing bacterium, is widely applied in bioleaching. The absence of an ideal selection marker has become a major obstacle to achieve high efficiency of the gene transfer system for A. caldus. Plasmid pJRD215, widely used in Acidithiobacillus spp., has severe drawbacks in molecular manipulations and potential biosafety issues due to its mobility. Therefore, finding a new selection marker and constructing new plasmids have become an urgent and fundamental work for A. caldus. Results Effective inhibitory effect of chloramphenicol on the growth of A. caldus was elucidated for the first time. The P2-cat gene cassette, including a chloramphenicol acetyltransferase gene (cat) from plasmid pACBSR and a promoter (P2) upstream of the tetracycline resistance gene on pBR322, was designed, chloramphenicol acetyltransferase was expressed in A. caldus, and the enzyme activity was assessed. A new vector pSDU1 carrying the replication and mobilization regions derived from pJRD215, the P2-cat gene cassette and a multiple cloning site from pUC19 was successfully constructed. Compared with pJRD215, pSDU1 had a 27-fold increase in electrotransformation efficiency (30.43±0.88×104 CFU/μg DNA for pSDU1 and 1.09±0.11×104 CFU/μg DNA for pJRD215), better carrying capacity and could offer more convenience for the restriction enzyme digestion. In addition, the generated plasmid pSDU1Δmob, a novel non-mobilizable derivative of pSDU1 lacking some DNA sequences involved in the mobilization process, had increased copy number in A. caldus and lost its mobility for biosafety considerations. Both pSDU1 and pSDU1Δmob exhibited stable maintenance in A. caldus within 50 passages. However, further deletion of orfEF region involved in regulating repAC operon resulted in a negative effect on transformation efficiency, copy number and stability of plasmid pSDU1ΔmobΔorfEF in A. caldus. Conclusion Chloramphenicol was proved to be an ideal selection marker for A. caldus. Novel plasmids carrying cat gene were constructed. The utilization of these vectors will undoubtedly facilitate efficient genetic manipulations and accelerate the research progress in A. caldus.